Price Integration of Major Vegetable Oils: A VECM Approach - Sari, Lela Novita; Feryanto; Pambudy, Rachmat (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Globally four main vegetable oils are soybean, rapeseed, sunflower, and palm oils. Although these oils compete, their prices typically trend in the same direction. This research aims to investigate the short-term and long-term pricing relationships among these four oils. After using the Vector Error Correction Model (VECM) for analysis, the study applies variance decomposition and impulse response approaches. Monthly data from January 2003 to December 2024 is included in the dataset. The results show that each vegetable oil's price is impacted by its historical price in the short run. On the other hand, the four oil prices show a long-term link over the long run, suggesting that they are cointegrated. It is evident from variance decomposition and impulse response function analysis that soybean oil's price significantly has a greater influence on the price of palm, sunflower, and rapeseed oils. The conclusion is that the price fluctuations of rapeseed oil, sunflower oil, and palm oil are largely driven by changes in soybean oil prices.